"It's always the contract!": legal risks and chances for geotechnical work in Central and South‐Eastern Europe. Issue 2 (6th June 2018) - MESIC, Muhamed
Abstract: Geotechnical work always involves a number of unique and significant legal risks affecting all stakeholders. These risks can and do cause major disturbances and deviations, including delays and cost explosions, and knowing them in order to properly assess and mitigate them is a key element for the success of any geotechnical project. Some jurisdictions, like Austria, can look back on more than 50 years of established legal principles and jurisprudence in this field, others in the broader region are just starting to look at and define the liability and extent of obligations of participants in geotechnical projects. The paper presents a comparative approach and explores legal concepts and contexts such as soil risk, standards for geotechnical investigation, liability for hazards or execution of geotechnical works under third‐party property from a perspective tailored for geotechnical practitioners in the region.